2003
DOI: 10.1053/jhep.2003.50064
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cellular resistance against Kupffer cell-derived oxidant stress: A novel concept of hepatoprotection by ischemic preconditioning

Abstract: Ischemic preconditioning (IP) triggers protection of the liver from prolonged subsequent ischemia. However, the underlying protective mechanisms are largely unknown. We investigated whether and how IP protects the liver against reperfusion injury caused by Kupffer cell (KC)-derived oxidants. IP before 90 minutes of warm ischemia of rat livers in vivo significantly reduced serum alanine aminotransferase (AST) levels and leukocyte adherence to sinusoids and postsinusoidal venules during reperfusion. This protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 48 publications
3
35
0
Order By: Relevance
“…Ischemic pre-conditioning is extensively documented to reduce I/R injury in a variety of organs including liver [10][11][12] . In our study, we demonstrated that IPC could attenuate hepatic I/R injury, indicated by reduced serum ALT and AST levels and improved tissue pathologic alteration as compared with I/R group.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic pre-conditioning is extensively documented to reduce I/R injury in a variety of organs including liver [10][11][12] . In our study, we demonstrated that IPC could attenuate hepatic I/R injury, indicated by reduced serum ALT and AST levels and improved tissue pathologic alteration as compared with I/R group.…”
Section: Discussionmentioning
confidence: 99%
“…The modulation of inflammatory response by hepatic IP has been also reported in different experimental models of warm and cold hepatic ischemia. IP reduces neutrophil accumulation, and the generation of ROS and proinflammatory cytokines including TNF and IL-1 from KC (13,97,98,108,109). The benefits of IP were also observed on hepatic microcirculation by inhibiting the effects of different vasoconstrictor mediators such as ETs, thus ameliorating sinusoidal perfusion and microvascular dysfunction (10,110).…”
Section: Steatosismentioning
confidence: 99%
“…To block KCs, a pretreatment with gadolinium chloride (GdCl 3 , 10 mg/kg b.w., 48 and 24 h before experiments) was performed in addition to LPS administration and after KC activation (n ¼ 5). 21 The LT receptor antagonist Ly171883 (20 mM, 30-60 min, n ¼ 5) and the TX receptor antagonist BM 13.177 (20 mM, 30-60 min, n ¼ 5) were given in addition to LPS pretreatment (1 mg/kg b.w., 3 h) and zymosan infusion (150 mg/ml, 40-46 min). The LT synthase inhibitor MK-886 (0.6 mg/kg b.w.)…”
Section: Induction Of Liver Fibrosis By Bile Duct Ligationmentioning
confidence: 99%